Determination of the Model for the Chemical Structure of Porous PECVD Low-k Films. (21st November 2014) - Verdonck, P.; Le, Quoc Toan; Devonport, J.; Huanca, D. R.; dos Santos Filho, S. G.; Conard, T.; Meersschaut, J.; Baklanov, M. R.; Van Elshocht, S.
Abstract : Scaling of Cu interconnect structures requires insulating materials with a low dielectric constant that also have adequate mechanical characteristics and good chemical resistance. These macro characteristics depend on the actual mechanical and chemical nanostructure of the porous low-k films. Unfortunately, there is no direct way to determine this exact nanostructure; e.g. neither Atom Probe nor Transmission Electron Microscopy are able to produce adequate images of an amorphous, porous low-k film. In this paper, we propose a new model for the chemical structure of PECVD low-k films: a strong hydrophobic layer, consisting of methyl groups covers the top surface of the porous film; besides, the pore walls are also covered with hydrophobic methyl groups. With this model, we are able to explain the macro characteristics of the low-k films. The model is supported by the test results obtained by modifying the top surface and immersing the pristine and modified films into diluted HF solutions.